ISLAM AND SOCIAL CHANGE IN INDONESIA: A VALUE AND LIFE PRACTICE PERSPECTIVE - Pestariama Berutu; Hasnil Aida (Jurnal Bilqolam Pendidikan Islam, 2026)
Indonesia is a country that has the largest Muslim population in the world. Currently, it is estimated that the number of Muslims reaches 207 million people, most of whom adhere to the Sunni sect of Islam. This large number implies that around 13% of Muslims worldwide live in Indonesia and also implies that the majority of the population in Indonesia adheres to Islam (almost 90% of the Indonesian population). However, even though the majority of the population is Muslim, Indonesia is not an Islamic country based on Islamic laws. In facing social changes in society, every devout religious follower will use the doctrine of his religious teachings to face all conditions that exist in his living environment. Islam acts as a value system that contains certain norms. The ongoing Islamization process has provided significant results both for Islam and for Indonesia. With this role of Islam, the dimensions of human life will be orderly and disciplined.